Force coordination strategies in on-water single sculling: Are asymmetries related to better rowing performance? - Warmenhoven, J.; Smith, R.; Draper, C.; Harrison, A. J.; Bargary, N.; Cobley, S. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Asymmetries of the rowing stroke cycle have been assessed with reference to kinematics and foot-force measures in laboratory testing environments. It remains unclear how asymmetries in propulsive kinetic measures are related to on-water rowing performance. A new approach for the evaluation of both global and local asymmetries across the entire movement was used to assess the continuous role of asymmetries and whether these change according to the level of competitive representation. Twenty-seven highly skilled female rowers (national and international competition level), rowing at 32 strokes per minute in a single scull boat, were evaluated. A symmetry index (SI) and functional data analysis (FDA) techniques were applied to a continuous difference time-series, which described fluctuating asymmetry in propulsive pin forces for each rower. Univariate ANOVAs revealed that differences in asymmetries were present as a factor of competition level for the SI and results of FDA. International athletes were more likely to utilize an asymmetry strategy with increased stroke-side (port-side) force early in the drive phase and increased bow-side (starboard) force through the second half of the drive. This was likely the result of international performers customizing their movement strategies relative to known boat mechanical offsets. The first half of the drive phase was also found to be an adaptive part of the rowing stroke cycle, suggesting asymmetries may have a functional role in successful execution of movements during the rowing stroke.